Study on the Relationship between Pore Structure and Uniaxial Compressive Strength of Cemented Paste Backfill by Using Air-Entraining Agent - Fengwen Zhao; Jianhua Hu; Dongjie Yang; Ye Kuang; Hongxing Xiao; Minghua Zheng; Xueliang Wang (Advances in Civil Engineering)
To control pores in the backfill, the air-entraining agents (AEAs) are used as an admixture to realize the pore structure changes under artificial action and explore the effect of pore structure on strength. Two AEAs at different dosages were added to the backfill. The relationship was then analyzed between them from the macro- and mesoscopic aspects. The results indicate that AEA can regulate pore structure changes of AEACPB. With the increase in AEA content, the total pore volume of different pore sizes in AEACPB increases, in which the proportion of big and medium pore gradually increases while the proportion of small pore gradually decreases. The AEACPB’s UCS is linearly negatively correlated with the porosity and pore percentage, which is the primary factor affecting the AEACPB of the pore structure. When the total pores’ volume in the AEACPB is constant, the influence of different pore structures differs. A higher proportion of small pores leads to a linear increase in strength; a higher proportion of medium pores leads to a linear decrease in strength; and a higher proportion of big pores leads to an exponential decrease in strength. And the fractal dimension has a linear negative correlation with the UCS by fractal theory analysis.